2019
DOI: 10.1111/medu.14031
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance of ambiguity and psychological well‐being in medical training: A systematic review

Abstract: Context:The prevalence of stress, burnout and mental health disorders in medical students and doctors is high. It has been proposed that there may be an association between levels of tolerance of ambiguity (ie an ability to tolerate a lack of reliable, credible or adequate information) in clinical work and psychological well-being within this population. The aims of this systematic review were: (i) to assess the nature and extent of the literature available, in order to determine if there is an association, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
128
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(137 citation statements)
references
References 44 publications
5
128
1
3
Order By: Relevance
“…Factors such as gender, religiosity, and social support have been shown to associated with burnout (or the lack thereof) (26)(27)(28)(29). Similar to the majority of studies dedicated to gender, the results of this study show that gender shares no relationship with burnout (46,47,(69)(70)(71).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Factors such as gender, religiosity, and social support have been shown to associated with burnout (or the lack thereof) (26)(27)(28)(29). Similar to the majority of studies dedicated to gender, the results of this study show that gender shares no relationship with burnout (46,47,(69)(70)(71).…”
Section: Discussionsupporting
confidence: 78%
“…Nonetheless, the potential for grit-a modi able factor (25) , represents an enticing target to mitigate burnout. Other factors which have been shown to affect psychological well-being and improved life satisfaction include tolerance for ambiguity (TFA) (26), religiosity (27,28), and social support (29).…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, the potential for grit-a modifiable factor [25], represents an enticing target to mitigate burnout. Other factors which have been shown to affect psychological well-being and improved life satisfaction include tolerance for ambiguity (TFA) [26], religiosity [27,28], and social support [29].…”
Section: Introductionmentioning
confidence: 99%
“…As such, different medical specializations and contexts may potentially be better suited to certain personality traits. Both tolerance of ambiguity and perfectionism are personality traits that vary across all persons, but not frequently researched in the context of medical education and thus are the focus of this study (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…While interest in TOA in the medical eld can be traced back to the early 1990s, studies have often led to con icting results, with some showing a larger, but non-statistically signi cant, TOA in 3 rd -year medical students ( rst year of clerkship experience in North American schools) (6) and others showing no difference (10). However, a recent review of 11 studies (Hancock and Mattick, 2020) concluded there was an association between a lower level of tolerance of ambiguity and lower psychological well-being amongst medical students and practicing doctors (3). Residents have been reported to have higher TOA compared to medical students (11).…”
Section: Introductionmentioning
confidence: 99%